Inhibiting NTRK2 signaling causes endometriotic lesion regression. Issue 1 (January 2021) - Lee, Hsiu-Chi; Lin, Shih-Chieh; Wu, Meng-Hsing; Tsai, Shaw-Jenq
Abstract : Endometriosis is a common gynecological disease in reproductive-age women. Although the hormone-dependent therapy is the first line treatment for endometriosis, it is not a curative regimen and associated with severe side-effects, which significantly decrease the life quality of affected individuals. To seek a target for treatment of endometriosis, we focused on plasma membrane proteins that are elevated in ectopic cells and exert beneficial effects in cell growth and survival. We performed bioinformatics analysis and identified the neurotrophic receptor tyrosine kinase 2 (NTRK2) as a potential candidate for treatment. The expression levels of NTRK2 were markedly upregulated in the lesions of clinical specimen as well as in the mouse endometriotic-like lesion. Mechanistic investigation demonstrated that upregulation of NTRK2 is induced by hypoxia in a hypoxia-inducible factor 1 alpha-dependent manner. Knockdown of NTRK2 or administration of ANA-12, a selective antagonist of NTRK2, significantly induced endometriotic stromal cells death, suggesting it may be a potential therapeutic agent. In vivo study using surgery-induced endometriosis mice model showed ANA-12 (1.5 mg/kg body weight) treatment induced apoptosis of endometriotic cells and caused the regression of ectopic lesions. Taken together, our findings suggest a possible mechanism responsible for the aberrant expression of NTRK2 in endometriotic lesions and this may be involved in the pathogenesis of endometriosis.